Anchoring Mn(IV) in multi pyridine modified mesoporous silica SBA-15: An efficient nanocatalyst for selective oxidation of sulfides to sulfoxides. (15th March 2020) - Hemmati, Saba; Hekmati, Malak; Salamat, Delafarin; Yousefi, Mohammad; Karmakar, Bikash; Veisi, Hojat
Graphical abstract: Abstract: In this current study we report the implementation of Mn(IV) grafted multipyridine linked melanine functionalized SBA-15/CCPy/Mn(OAc)2 as a novel high surface area nanocatalyst. The melamine linked multipyridine ligand was introduced over mesoporous SBA-15 to ensure the strong chelation of Mn(OAc)2 in order to deploy as active site. The structural features of the so designed material were properly analyzed with SEM, TEM, EDX, ICP-AES and N2 adsorption-desorption isotherm techniques. Catalytic behavior of the nanocomposite was investigated in the chemoselective oxidation of sulfides to sulfoxides using H2 O2 as a mild oxidant under solvent-free conditions at room temperature resulting very good yields. The catalyst was reused up to 8 consecutive cycles without significant leaching and reduced catalytic performance.